A Model of Vegetative Stage of Baby Cucumber Using Artificial Neural Network - Tamrin .; K. B. Seminar; H. Suhardiyanto; S. Hardjoamidjojo (Jurnal Keteknikan Pertanian, 2005)
A model of how plant reacts to their micro climate is of great importance to control the physical micro climate around the plant and to other major input problems (such as rutinition intake). Artificial Neural Network (ANN) can be utilized to model a plant reaction to their microclimate in a more objective facshion by applying the ANN to measured data, and not from a pre-assumed model structure. This paper discusses a model of the plant response (the ratio of canopy area-stem diameter of baby cucumber) and the loss of nutrition solution as output and nutrition solution intake and microclimate (temperature, humidity, and irradiation) as input by using artificial neural network of dynamic response.